Development of a new haptic perception instrument: a pilot study - Nascimento, Leonardo Penteado; Martini, Joyce; Voos, Mariana Callil; Chien, Hsin Fen; Caromano, Fátima Aparecida (Arquivos de Neuro-Psiquiatria, 2016)
ObjectiveHand sensory tests do not consider distinct physiological receptors, nor detect normal range variations concerning developmental or pathological changes. We developed an instrument with a set of tests with timing and scoring for assessing haptic perception, which is the interaction between sensory and motor systems, in surfaces exploration, by moving hands.MethodFirstly, group meetings were set for test/manual conception and materials testing. The test/manual were submitted to 30 reviewers in 3 stages (10 reviewers on each stage).RESULTSThe Hand Haptic Perception Instrument (HHPI) evaluates hand sensorimotor performance on six domains: depression, elevation, texture, compressibility, weight (barognosis) and form perception. Each domain requires specific materials. Score ranges from 0 to 57, being 0 the worst rating.ConclusionThis methodological process allowed the development of six domains and instructions to assess haptic perception. This version of HHPI is a pilot model. Further studies will determine reliability and normality ranges.
Keywords: touch perception; form perception; weight perception; evaluation; hands